A Retrospective Study on the Significance of Liver Biopsy and Hepatitis B Surface Antigen in Chronic Hepatitis B Infection. Issue 8 (February 2016) - Zeng, Da-Wu; Zhang, Jie-Min; Liu, Yu-Rui; Dong, Jing; Jiang, Jia-Ji; Zhu, Yue-Yong
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: To investigate changes in the HBV replication level along with the natural course of chronic HBV infection and to examine the accuracy of the immune tolerant phase defined by the serological profile. A total of 390 chronic HBV-infected patients were retrospectively recruited for this study. They were classified into immune-tolerance (IT), immune-clearance (IC), low-replicative (LR), and HBeAg-negative hepatitis (ENH) phases according to serological profiles (single-standard, SS) or dual-standard (DS) with the inclusion of liver histology. Serum HBV DNA and HBsAg were quantitatively measured, and liver histology was quantitatively analyzed. The accuracy of the SS-defined IT phase was low, and active pathological changes were detected in 56 of 112 SS-defined IT patients. DS-defined IT patients had higher HBsAg levels ( P = 0.0002) than the SS-defined patients. The quantitative HBsAg level can help identify SS-defined IT patients with potential liver injury. The area under the received operating characteristic curve for predicting the DS-defined IT phase was 0.831 (HBsAg 4.398 log IU/mL; sensitivity 87.5%; specificity 73.2%). HBV DNA was reduced by 4 logs, whereas HBsAg was only decreased by 2 logs with HBeAg positive to negative phase conversion. Approximately half of IT patients defined by SS may have medium or severe liver injury. Quantitative measurement of the HBsAg level can help identify SS-defined IT patients with potential liver injury.